Correlates of vaccine protection against Mycobacterium avium sub-species paratuberculosis infection revealed in a transcriptomic study of responses in Gudair® vaccinated sheep - Purdie, Auriol C.; Plain, Karren M.; Pooley, Hannah; Begg, Douglas J.; de Silva, Kumudika; Whittington, Richard J. (Frontiers in Veterinary Science, 2022)
A critical hindrance in the development of effective vaccine strategies to combat infectious disease is an understanding of the protective correlates of immunity and of host factors involved in a successful adaptive immune response. Often vaccine formulations are developed empirically, with little or no understanding of the underlying immunological mechanisms by which they induce protective immunity. Gudair® is a widely used vaccine in sheep and goats for controlling spread of Mycobacterium avium sub-species paratuberculosis (MAP) infections and reduces mortality by up to 90%. Here, using an experimental infection model in sheep, we have utilised a transcriptomics approach to identify gene expression changes in vaccinated, MAP-exposed Merino sheep with a protective response in comparison to those vaccinated animals that failed to develop immunity to MAP infection. This methodology facilitated an overview of gene-associated functional pathway adaptations using an in-silico analysis approach. Most significantly, we have identified a set of genes induced in the vaccine-protected animals and confirmed stability of expression in samples obtained from naturally exposed commercially maintained sheep. We propose these genes as correlates of vaccine induced protection.